Carbon-carbon composite material as well as preparation method and application thereof

By reacting chopped carbon fibers, carbon sources and metal sources at high temperature under an inert atmosphere, a carbon-carbon composite material with multi-layer graphite sheets and nanometal particles was prepared, which solved the problem of single form and single composition of carbon-carbon composite materials in the prior art, and achieved high conductivity and electrochemical activity of the material.

CN119841643AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202311348666.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

The finished product form of existing carbon-carbon composite materials is relatively single, with only carbon the main constituent element, and there is no research on the high aspect ratio and fiber rod shape.

Method used

A composite material was prepared by reacting chopped carbon fibers, carbon sources and metal sources under an inert atmosphere at 1500-3500°C to which a single carbon fiber surrounded a multi-layer graphite sheet and filled with nanometal particles.

Benefits of technology

A carbon-carbon composite material composed of a cluster of layered graphite sheets with concentric circular structures on the microscopic scale is realized. It contains a variety of metal and non-metal elements inside, showing a uniform distribution at the atomic scale, enhancing the conductivity and electrochemical activity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841643A_ABST
    Figure CN119841643A_ABST
Patent Text Reader

Abstract

The invention relates to the field of new materials, and discloses a carbon-carbon composite material as well as a preparation method and application thereof. In the field, the carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite flakes surrounding the periphery of the single carbon fiber, the space between any two adjacent layers of graphite flakes is filled with nano metal particles, and the nano metal particles contain IA group metal elements, VB group metal elements, VIB group metal elements and VIII group metal elements. The carbon-carbon composite material has the advantages that the carbon-carbon composite material is composed of layered graphite sheet clusters with concentric circle structures on the microscopic scale, contains various types and contents of metal and non-metal elements and is uniformly distributed under the atomic scale, further, the carbon-carbon composite material also contains IA group metal elements, VB group metal elements, VIB group metal elements and VIII group metal elements at the same time, and the carbon-carbon composite material has the advantages that the carbon-carbon composite material can be used for preparing a carbon-carbon composite material; better electrochemical activity is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new materials, and in particular to a carbon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Carbon fiber has comprehensive properties such as high tensile strength, high tensile modulus, low density, high temperature resistance, ablation resistance, corrosion resistance, high electrical and thermal conductivity, low thermal expansion, self-lubrication and good biocompatibility. Carbon fiber is widely used in aerospace, automotive industry, building energy and sports equipment. He Fu wrote in the fifth chapter of Carbon Fiber and Graphite Fiber (first edition in September 2010): Graphite fiber generally refers to carbon fiber with a carbon content of more than 99%. Carbon fiber can be obtained by high-temperature graphitization at 2200-3000℃. Graphite fiber not only has a high carbon content, but also has a high tensile modulus. Graphite fiber has excellent properties such as low thermal expansion coefficient, good thermal stability and dimensional stability. Therefore, it is used to manufacture rigid, thin and dimensionally stable composite materials and is widely used in the field of aerospace based on spacecraft. For example, the horn antenna of artificial satellites is made of high-model carbon fiber composite materials to ensure dimensional stability in the space environment with alternating temperature.

[0003] Carbon-carbon (C / C) composite material refers to a multiphase structural material (CN112125690A) with carbon fiber or its fabric as the reinforcing phase, pyrolytic carbon infiltrated by chemical vapor phase or resin carbon or asphalt carbon infiltrated by liquid phase carbonization as the matrix. It has extremely high specific strength and specific modulus. It can be used above 2000°C in an inert atmosphere, and the mechanical properties are not reduced. It has characteristics that are unmatched by any other material. C / C composite materials are non-melting and non-combustible, and they ablate evenly. They are widely used in the outer wall materials of space shuttles, missile nose cones, and engine nozzles. C / C composite materials are excellent thermal conductive materials with small thermal expansion coefficients, friction resistance and wear resistance, and are widely used in aircraft brake devices. C / C composite materials are usually prepared by using a preform made of carbon fiber filaments, or a short-cut carbon fiber composite matrix carbon as an embryo, and densifying it through liquid phase impregnation and carbonization or chemical vapor deposition and chemical vapor infiltration.

[0004] The manufacture of carbon-carbon composites is an integration of high-temperature technology and high-temperature equipment. The key technology of its continuous graphitization preparation is to inhibit and regulate the high-temperature oxidation and high-temperature biochemistry (evaporation) of graphite heating elements and running fibers. Carbon-carbon composites have different forms of carbon materials in macroscopic terms because of different forms of stacking / arrangement in the three-dimensional space. These various forms of carbon materials are composed of microcrystals of different sizes and diverse orientations and stacking states. The nanocarbon fibers grown by catalytic vapor phase have different shapes. Different catalysts and raw materials produce tubular, herringbone and flat nanocarbon fibers with different structures.

[0005] CN111807853A discloses a preparation process and application of carbon-carbon composite parts, which uses carbon fiber, vapor deposition carbon and impregnation carbon composite, can maintain good mechanical, thermal and friction and wear properties at high temperature, reduce costs by 50%, and can be mass-produced. CN112125690A uses flake graphite and UV silica gel to prepare a mixed colloid, fills it in the middle of the mixed layer of carbon fiber and glass fiber to prepare an intermediate, and prepares a carbon-carbon composite material by hot pressing, curing and drying. The composite material has the advantages of high tensile strength and high elasticity. CN112679950A discloses a preparation method of a flexible carbon-carbon composite material, after covering the surface of the carbon fiber cloth with a thermosetting resin film, hot pressing and curing are carried out, and the composite material is obtained after carbonization in an inert atmosphere. The method has the advantages of short processing time, simple process, no need for high-pressure equipment, and high production efficiency, and can realize industrial production. CN113175565A discloses a thin-walled high-strength carbon-carbon composite pipe and a preparation method thereof, the pipe comprises a pipe body formed by laminating carbon cloth, a binder, and a CVD layer, and a dense layer located on the inner surface of the pipe body, the pipe has the advantages of reducing the wall thickness while maintaining the strength. CN113636854A discloses a carbon-carbon composite material with deposited carbon nanotubes, wherein chopped carbon fibers are embedded in a carbon matrix and carbon fibers, and carbon nanotubes are deposited between the two, which has the advantages of significantly improving the mechanical properties and anti-oxidation properties of the carbon-carbon composite material. CN113636855A discloses an internal anti-oxidation carbon-carbon composite material, comprising a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, silicon carbide, zirconium oxide, and aluminum oxide, which has the advantages of improving the ablation resistance and service life of the composite material. CN113683437A discloses a carbon-carbon composite material containing refractory metal, including a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, a metal zirconium-fullerene composite nanopowder, and silicon-rich silicon carbide, which has the advantages of improving the ablation resistance, service life and oxidation resistance of the composite material. CN115180969A discloses a high thermal conductivity carbon-carbon composite material and a preparation method thereof, which produces graphene / AIN reinforcement on the surface and inside of a carbon fiber needle-punched preform by electrophoresis, impregnates in benzoxazine resin, and after heat curing and carbonization at normal pressure, has the advantages of excellent mechanical properties and good thermal conductivity. CN115231941A relates to a carbon-carbon composite material for ultra-high temperature environment and a preparation method thereof, including a carbon matrix, a carbon fiber reinforcement, an ultra-high temperature ceramic and a carbon nanotube. The prepared carbon-carbon composite material has the advantages of excellent mechanical properties, high temperature ablation resistance and good thermal conductivity. CN213628313U discloses a carbon-carbon composite material plate, which has the advantages of light weight and high strength, high thermal conductivity and low expansion, good friction performance, good thermal shock resistance and high dimensional stability.

[0006] Existing public patent research shows that most of the current research work on C / C composite materials focuses on the improvement and optimization of their preparation process; focusing on solving the functional properties and application technical problems of C / C composite materials. However, the finished product form of C / C composite materials disclosed in the prior art is relatively simple, and the main component element is only carbon, and there is no report on C / C composite materials with high aspect ratio and fiber rod morphology. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem that the existing technology has carbon-carbon composite materials with a single finished product form, the main component element is only a single carbon element, and there is no carbon-carbon composite material with a high aspect ratio and a fiber rod-like form. A carbon-carbon composite material and a preparation method and application are provided. The carbon-carbon composite material has the advantage of being composed of layered graphite flake clusters with a concentric circle structure on a microscopic scale, containing many types and amounts of metal and non-metal elements inside, and showing a uniform distribution at the atomic scale.

[0008] In order to achieve the above object, the present invention provides a carbon-carbon composite material, which includes a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, wherein nano-metal particles are filled between any two adjacent layers of graphite sheets.

[0009] The nano metal particles contain metal elements of Group IA, Group VB, Group VIB and Group VIII.

[0010] Preferably, the carbon-carbon composite material contains 45-92 wt% of carbon, 1.6-52 wt% of Group IA metal elements, 0.1-1 wt% of Group VB metal elements, 0.05-3 wt% of Group VIB metal elements and 2.2-33 wt% of Group VIII metal elements.

[0011] Preferably, the nano metal particles contain sodium, potassium, nickel, lithium, platinum, iron, chromium and vanadium.

[0012] Preferably, the carbon-carbon composite material contains 45-92 weight % of carbon, 0.7-18 weight % of sodium, 0.5-18 weight % of potassium, 0.5-15 weight % of nickel, 0.4-13 weight % of lithium, 1-10 weight % of platinum, 0.7-8 weight % of iron, 0.05-3 weight % of chromium and 0.1-1 weight % of vanadium.

[0013] Preferably, the carbon-carbon composite material contains 50-90 weight % of carbon, 1-15 weight % of sodium, 1-15 weight % of potassium, 1-10 weight % of nickel, 1-10 weight % of lithium, 1-5 weight % of platinum, 1-5 weight % of iron, 0.1-1 weight % of chromium and 0.1-0.5 weight % of vanadium.

[0014] Preferably, the number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, preferably 8-12 layers.

[0015] Preferably, the diameter of the single carbon fiber is 4-8 um, preferably 4.5-7.5 um.

[0016] Preferably, the length of the single carbon fiber is 2-10 mm, preferably 3-9 mm.

[0017] Preferably, the thickness of the multi-layer graphite sheet gradually increases from the inside to the outside.

[0018] Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:1.

[0019] Preferably, the carbon-carbon composite material is in a straight line or a curved shape.

[0020] Preferably, at least part of the surface of the carbon-carbon composite material is in a bamboo-node shape and / or a convex shape.

[0021] Preferably, the diameter of the carbon-carbon composite material is 0.05-1 mm, preferably 0.1-0.3 mm.

[0022] Preferably, the length of the carbon-carbon composite material is 0.1-10 mm, preferably 1-5 mm.

[0023] Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1.

[0024] Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak is 0.2-0.9:1.

[0025] A second aspect of the present invention provides a method for preparing a carbon-carbon composite material, the method comprising: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 50-500 mL / min;

[0026] The metal source includes a Group IA metal source, a Group VB metal source, a Group VIB metal source and a Group VIII metal source.

[0027] Preferably, the weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:1.

[0028] Preferably, the weight ratio of the Group IA metal source, the Group VB metal source, the Group VIB metal source and the Group VIII metal source is 50-500:1:3-10:30-350.

[0029] Preferably, the metal source contains a sodium source, a potassium source, a nickel source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source.

[0030] Preferably, the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 20-180:20-180:20-150:10-100:10-100:5-80:3-10:1.

[0031] Preferably, the sodium source is selected from Na 2 CO 3 、NaHCO 3 、NaNO 3 , one or more of NaCl and NaF.

[0032] Preferably, the potassium source is selected from KCl, K 2 CO 3 , one or more of KF and KOH.

[0033] Preferably, the nickel source is selected from NiO, Ni(OH) 2 、NiF 2 and NiCl 2 One or more of the following.

[0034] Preferably, the lithium source is selected from LiF, Li 2 O, one or more of LiOH and LiCl.

[0035] Preferably, the platinum source is selected from PtO, PtO 2 and Pt(OH) 2 One or more of the following.

[0036] Preferably, the iron source is selected from FeO, Fe 2 O 3 , Fe 3 O 4 、Fe(OH) 2 、Fe(OH) 3 、FeCl 2 、FeCl 3 and FePO 4One or more of the following.

[0037] Preferably, the chromium source is selected from CrO 3 , Li 2 CrO 4 , K 2 CrO 4 and BaCrO 4 One or more of the following.

[0038] Preferably, the vanadium source is selected from VO, V 2 O 3 , VO 2 and V 2 O 5 One or more of the following.

[0039] Preferably, the carbon source is carbonized resin and / or graphite.

[0040] Preferably, the graphite is amorphous graphite.

[0041] Preferably, the reaction temperature is 1500-3000°C.

[0042] Preferably, the reaction time is 12-720 hours, more preferably 24-120 hours.

[0043] Preferably, the volume flow rate of the inert atmosphere is 100-300 mL / min.

[0044] Preferably, the length of the chopped carbon fibers is 0.1-10 mm, preferably 1-5 mm.

[0045] Preferably, the specification of the chopped carbon fiber is 12-320K, preferably 12-48K.

[0046] Preferably, the carbon content of the chopped carbon fibers is 85-95% by weight.

[0047] A third aspect of the present invention provides a carbon-carbon composite material prepared by the above method.

[0048] A fourth aspect of the present invention provides an application of the above carbon-carbon composite material in a graphite electrode material.

[0049] The carbon-carbon composite material described in the present invention has the advantage of being composed of layered graphite flake clusters with a concentric circle structure on a microscopic scale, containing various types and amounts of metal and non-metal elements inside, and showing a uniform distribution at the atomic scale. Furthermore, the carbon-carbon composite material also contains metal elements of Group IA, Group VB, Group VIB and Group VIII, and has better electrochemical activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a schematic diagram of the macroscopic morphology of the carbon-carbon composite material of Example 1;

[0051] Figure 2 This is the energy spectrum of Na element inside the carbon-carbon composite material of Example 1;

[0052] Figure 3 This is the K element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0053] Figure 4 This is the Ni element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0054] Figure 5 This is the Li element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0055] Figure 6 This is the Pt element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0056] Figure 7 This is the energy spectrum of Fe element inside the carbon-carbon composite material of Example 1;

[0057] Figure 8 This is the Cr element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0058] Fig. 9 This is the V element spectrum diagram inside the carbon-carbon composite material of Example 1;

[0059] Fig.10 This is a schematic diagram of the cross-sectional morphology of the carbon-carbon composite material of Example 1; DETAILED DESCRIPTION

[0060] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0061] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0062] In one aspect, the present invention provides a carbon-carbon composite material, comprising a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, wherein nano-metal particles are filled between any two adjacent layers of graphite sheets.

[0063] The nano metal particles contain metal elements of Group IA, Group VB, Group VIB and Group VIII.

[0064] The carbon-carbon composite material provided by the present invention has a special microscopic morphology, wherein the center of the carbon-carbon composite material is a single carbon fiber, and the periphery of the single carbon fiber is surrounded by a plurality of graphite sheets in a concentric circle structure. At the same time, the carbon-carbon composite material contains nano-metal particles (non-carbon elements), and the nano-metal particles are evenly distributed between any two adjacent graphite sheets.

[0065] In the present invention, in order to further improve the performance of the carbon-carbon composite material, in a preferred case, the nano metal particles contain metal elements of Group IA, Group VB, Group VIB and Group VIII.

[0066] In a preferred embodiment of the present invention, in order to enhance the electrical conductivity and electrochemical activity of the carbon-carbon composite material, in a preferred embodiment, the content of each element in the carbon-carbon composite material needs to be limited.

[0067] Therefore, preferably, the carbon-carbon composite material contains 45-92 wt% of carbon, 1.6-52 wt% of Group IA metal elements, 0.1-1 wt% of Group VB metal elements, 0.05-3 wt% of Group VIB metal elements and 2.2-33 wt% of Group VIII metal elements.

[0068] Further preferably, the nano metal particles contain sodium, potassium, nickel, lithium, platinum, iron, chromium and vanadium. When containing the above metal elements, the electrode material can have excellent conductivity, improve its electrochemical activity, and be beneficial to the electrocatalytic reaction of the graphite electrode.

[0069] Preferably, the carbon-carbon composite material contains 45-92 weight % of carbon, 0.7-18 weight % of sodium, 0.5-18 weight % of potassium, 0.5-15 weight % of nickel, 0.4-13 weight % of lithium, 1-10 weight % of platinum, 0.7-8 weight % of iron, 0.05-3 weight % of chromium and 0.1-1 weight % of vanadium.

[0070] Preferably, the carbon-carbon composite material contains 50-90 weight % of carbon, 1-15 weight % of sodium, 1-15 weight % of potassium, 1-10 weight % of nickel, 1-10 weight % of lithium, 1-5 weight % of platinum, 1-5 weight % of iron, 0.1-1 weight % of chromium and 0.1-0.5 weight % of vanadium.

[0071] In the present invention, the number of layers of graphite sheets with a concentric structure surrounding the outer periphery of the single carbon fiber is relatively large. Specifically, the number of layers of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, preferably 8-12 layers, and specifically can be 8 layers, 9 layers, 10 layers, 11 layers or 12 layers. When the number of layers of graphite sheets with a concentric structure surrounding the outer periphery of the single carbon fiber is relatively large, the nano-metal particles can be distributed more evenly between the graphite sheets, and the size of the carbon-carbon composite material can be maintained stable.

[0072] In the present invention, the diameter of the single carbon fiber can be a conventional choice in the art. Preferably, the diameter of the single carbon fiber is 4-8 um, and more preferably 4.5-7.5 um.

[0073] The length of the single carbon fiber is comparable to the length of the carbon-carbon composite material. Preferably, the length of the single carbon fiber is 2-10 mm, preferably 3-9 mm.

[0074] The microscopic morphology of the carbon-carbon composite material of the present invention is quite special. It can be seen from a scanning electron microscope that, preferably, the thickness of the multilayer graphite sheets gradually increases from the inside to the outside, which can improve the stability of the concentric circle structure of the carbon-carbon composite material.

[0075] The approximate ratio of the content of carbon fiber and graphite in the carbon-carbon composite material can be inferred from the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber. In a preferred embodiment, the ratio of the total thickness of the multilayer graphite sheet to the diameter of the single carbon fiber can be 1-100:1, specifically 1:1, 20:1, 40:1, 60:1, 80:1 or 100:1. Limiting the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber within this range can enhance its conductivity and electrochemical activity.

[0076] In the present invention, the appearance of the carbon-carbon composite material is not limited and can be in various forms. Specifically, the carbon-carbon composite material is linear or curved as a whole.

[0077] The carbon-carbon composite material provided by the present invention may also contain carbon particles that exist independently or in aggregated form, wherein the carbon particles are evenly distributed on the surface of each layer of graphite sheets. Preferably, the particle size of the carbon particles is 0.02-2 mm.

[0078] In the present invention, due to the presence of nano-metal particles or nano-metal particles and carbon particles, the diameter of the carbon-carbon composite material is not uniform. Specifically, at least part of the surface of the carbon-carbon composite material is in a bamboo-like shape and / or a convex shape.

[0079] In a preferred embodiment of the present invention, the diameter of the carbon-carbon composite material is 0.05-1 mm, preferably 0.1-0.3 mm; the length of the carbon-carbon composite material is 0.1-10 mm, preferably 1-5 mm.

[0080] In the present invention, after characterization by Raman spectrum, the peak intensity ratio of the D peak to the G peak of the carbon-carbon composite material can be 0.07-0.3:1. When the peak intensity ratio of the D peak to the G peak is within this range, the smaller the carbon atom lattice defect is, the higher the conductivity of the carbon-carbon composite material is.

[0081] In the present invention, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak can be 0.2-0.9:1. When the peak intensity ratio of the 2D peak to the G peak is within this range, the graphitization degree of the carbon-carbon composite material is relatively complete and the conductive performance is relatively high.

[0082] In a specific embodiment, the carbon-carbon composite material of the present invention is gray or black.

[0083] The carbon-carbon composite material of the present invention also contains a small amount of other metal elements, including zinc, manganese, silver, barium, copper, magnesium, lead and strontium, and the content of each metal element is less than 0.001% by weight.

[0084] A second aspect of the present invention provides a method for preparing a carbon-carbon composite material, the method comprising: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 50-500 mL / min;

[0085] The metal source includes a Group IA metal source, a Group VB metal source, a Group VIB metal source and a Group VIII metal source.

[0086] The method of the present invention is simple and easy to operate, and only requires mixing and contacting chopped carbon fibers, a carbon source and a metal source of a specific family for reaction.

[0087] In the present invention, in order to obtain a carbon-carbon composite material with an appropriate ratio of carbon element to metal element content, a large number of graphite sheets surrounding the diameter of a single carbon fiber, and excellent conductive properties, the weight ratio of the metal source, the carbon source and the chopped carbon fiber can be appropriately controlled.

[0088] Preferably, the weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:1.

[0089] In the present invention, the metal source is used to generate nano-metal particles and fill them between graphite sheets. Therefore, the metal source contains Group IA metal source, Group VB metal source, Group VIB metal source and Group VIII metal source.

[0090] Preferably, the weight ratio of the Group IA metal source, the Group VB metal source, the Group VIB metal source and the Group VIII metal source is 50-500:1:3-10:30-350.

[0091] In a preferred case, the metal source contains a sodium source, a potassium source, a nickel source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source. When these metal elements exist at the same time, they not only provide a carrier for the electrochemical catalytic reaction and a medium for charge transfer, but the physical space effect caused by the metal particles is also beneficial to the diffusion of electrochemical reactants and the discharge of products.

[0092] Preferably, the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 20-180:20-180:20-150:10-100:10-100:5-80:3-10:1.

[0093] In the present invention, the sodium source can be a conventional choice in the art, and can be a sodium salt, sodium oxide or sodium hydroxide, and can be specifically selected from Na 2 CO 3 、NaHCO 3 、NaNO 3 , one or more of NaCl and NaF.

[0094] In the present invention, the potassium source can be a conventional choice in the art, and can be a potassium salt, potassium oxide or potassium hydroxide, and can be specifically selected from KCl, K 2 CO 3 , one or more of KF and KOH.

[0095] In the present invention, the nickel source can be a conventional choice in the art, and can be a nickel salt, nickel oxide or nickel hydroxide, and can be specifically selected from NiO, Ni(OH) 2 、NiF 2 and NiCl 2 One or more of the following.

[0096] In the present invention, the lithium source can be a conventional choice in the art, and can be a lithium salt, a lithium oxide or a lithium hydroxide, and can be specifically selected from LiF, Li 2 O, one or more of LiOH and LiCl.

[0097] In the present invention, the platinum source can be a conventional choice in the art, and can be a platinum salt, a platinum oxide or a platinum hydroxide, and can be specifically selected from PtO, PtO 2 and Pt(OH) 2 One or more of the following.

[0098] In the present invention, the iron source can be a conventional choice in the art, and can be an iron salt, an iron oxide or an iron hydroxide, and can be specifically selected from FeO, Fe 2 O 3 , Fe 3 O 4 、Fe(OH) 2 、Fe(OH) 3 、FeCl 2 、FeCl 3 and FePO 4 One or more of the following.

[0099] In the present invention, the chromium source can be a conventional choice in the art, and can be a chromium salt, chromium oxide or chromium hydroxide, and can be specifically selected from CrO 3 , Li 2 CrO 4 , K 2 CrO 4 and BaCrO 4 One or more of the following.

[0100] In the present invention, the vanadium source can be a conventional choice in the art, and can be a vanadium salt, a vanadium oxide or a vanadium hydroxide, and can be specifically selected from VO, V 2 O 3 , VO 2 and V 2 O 5 One or more of the following.

[0101] In the method of the present invention, the role of the carbon source is to form a graphite sheet on the periphery of a single carbon fiber. The carbon source can be a conventional choice in the art, specifically, the carbon source can be a carbonized resin and / or graphite. Preferably, the carbonized resin is a resin carbide obtained after high-temperature carbonization. Preferably, the graphite is amorphous graphite.

[0102] In order to ensure that the chopped carbon fibers, the carbon source and the metal source can generate the carbon-carbon composite material of the aforementioned structure, the reaction needs to be carried out under inert atmosphere conditions. Specifically, the inert atmosphere is nitrogen and / or an inert gas; the purity of nitrogen and the inert atmosphere are both greater than 99.9% by volume, and the oxygen content in the inert atmosphere is less than 50 ppm.

[0103] In the present invention, the reaction can be carried out in a conventional high-temperature furnace. Specifically, isostatic graphite or highly oriented graphite is used as a heating element in the high-temperature furnace. Preferably, the high-temperature furnace is connected to the tail gas recovery system through a pipeline, and a valve is provided on the pipeline connecting the high-temperature furnace and the tail gas recovery system. The inner diameter of the pipeline is between 5-20 mm, and the valve is fully open. A filter screen is provided before the valve along the gas flow direction, and the selection of the pipeline, the filter screen and the valve meets the temperature resistance requirements.

[0104] In a preferred embodiment of the present invention, the reaction temperature is 1500-3000° C. In a specific embodiment, the reaction temperature can be 1500° C., 2000° C., 2500° C. or 3000° C. In order to prepare a carbon-carbon composite material with a graphite structure, the relationship between the growth rate and temperature of the metal particles and the operating economy of the high-temperature furnace are considered at the same time, so it is more appropriate to control the reaction temperature within the above range.

[0105] Preferably, the reaction time is 12-720 hours, more preferably 24-120 hours, specifically, the reaction time can be 24 hours, 50 hours, 75 hours, 100 hours or 120 hours.

[0106] In the preferred embodiment of the present invention, the volume flow rate of the inert atmosphere is 100-300 mL / min, specifically 100 mL / min, 150 mL / min, 200 mL / min, 250 mL / min or 300 mL / min. When the gas flow rate is low, the adsorbed oxygen on the surface of the raw material cannot be completely replaced, resulting in oxidation and etching of the raw material, affecting the preparation effect of the carbon-carbon composite material; when the gas flow rate is high, the chopped carbon fiber is suspended and vibrated, and the gasified carbon and nano-metal particles cannot adhere and grow in a stable state.

[0107] In the present invention, the single carbon fiber in the center of the carbon-carbon composite material is formed by chopped carbon fiber. In a specific embodiment, the length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification of the chopped carbon fiber is 12-320K, preferably 12-48K.

[0108] In the present invention, the carbon content of the chopped carbon fibers is 85-95% by weight, and can be specifically 85% by weight, 90% by weight, or 95% by weight.

[0109] A third aspect of the present invention provides a carbon-carbon composite material prepared by the above method.

[0110] A fourth aspect of the present invention provides an application of the above carbon-carbon composite material in a graphite electrode material.

[0111] The carbon-carbon composite material described in the present invention can be further processed as a raw material. The processing methods include but are not limited to blending / extrusion / granulation, strip making, grinding / crushing, and roasting. The types and contents of the constituent elements of the material products manufactured by the above-mentioned processing methods, as long as they fall within the scope specified in the present invention, belong to the protection scope of the present invention. It is further clarified that as long as the types and contents of the elements contained are within the specified range of the present invention, whether it is a raw material or a finished product, and the shape of the material is not limited to a fiber shape; and it is not limited to the processing process of the material, it is within the protection scope of the present invention.

[0112] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto. In the following examples, the carbonized resin powder used is YKD-508 hemoperfusion carbonized resin (carbon skeleton spherical porous adsorption resin) purchased from Henan Yinkai New Materials Co., Ltd.

[0113] The test method adopted by the present invention comprises:

[0114] 1. The surface and cross-sectional morphology of the carbon-carbon composite materials prepared in the examples and comparative examples were observed using a ZEISS Merlin field emission scanning electron microscope, wherein the test conditions included: an acceleration voltage of 20 to 30 kV, and an electron beam current of 10 pA to 40 / 100 / 300 nA.

[0115] 2. The element types, distribution states and particle sizes of the carbon-carbon composite materials prepared in the examples and comparative examples were analyzed using an X-ray spectrometer configured with a field emission scanning electron microscope from German ZEISS Merlin. The surface scanning mode test conditions included: an acceleration voltage of 20 to 30 kV, an effective working area of ​​the probe of 150 mm 2 , element range Be~U, detection limit ≈0.1wt.%.

[0116] 3. Raman imaging analysis of the cross section of carbon-carbon composite materials: A laser micro-Raman spectrometer (micro-Raman spectroscopy analysis, RENISHAW, inVia Raman microscope, UK, 532nm line, helium-neon laser radiation model: QONTOR) is used to observe the cross-sectional morphology of the carbon-carbon composite materials prepared in the embodiments and comparative examples, and Raman imaging analysis of the cross-sectional morphology is performed, which can achieve high-sensitivity spectral analysis under high-resolution conditions. The specific method includes: directly breaking the carbon-carbon composite material, observing the morphology after the cross section appears, using Live TrackTM technology to focus in real time, and collecting each point in the test process in a focused state. The coordinates of each point in the Z-axis direction will be recorded to form a height imaging map of the surface, and the Raman imaging results can be superimposed on the height map. The in-situ Raman imaging area: 70um*70um, step length 1um, the recording range of the Raman spectrum is 400-3100cm -1 The integration time of each spectrum is 100s. The cross-sectional morphology of the fibrous composite material was observed under a 20x objective lens, and the Raman spectrum was collected somewhere in the 1um*1um area. The spectrum has a wavelength of 1350cm -1 Nearby D peak, 1582cm -1 The nearby G peak, and 2699cm -1 The 2D peak nearby; also use Raman imaging to see the intensity distribution of the D peak at different points.

[0117] 4. The types and contents of non-carbon elements in the carbon-carbon composite materials prepared in the examples and comparative examples were tested using an inductively coupled plasma emission spectrometer.

[0118] The main instruments and reagents are as follows:

[0119] (1) Varian 725-ES inductively coupled plasma optical emission spectrometer;

[0120] (2) Haoyue HMF1600-40 box-type furnace;

[0121] (3) Labtech Digiblock ST36 electric heating digestion instrument;

[0122] (4) Multi-element standard solution: 1000ug / mL (Steel Research Institute of Testing Technology Co., Ltd.); praseodymium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); vanadium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); The ultrapure water used in the experiment was prepared by the Genie Purist intelligent ultrapure water system of Lefeng (resistivity = 18.2MΩcm, 25°C); hydrogen peroxide (30wt%), hydrochloric acid, nitric acid, and hydrofluoric acid were all of premium grade purity; sulfuric acid was of process ultrapure purity (Sinopharm Chemical Reagent Co., Ltd.); liquid argon (Chart Cryogenic Engineering Systems (Changzhou) Co., Ltd.).

[0123] The working conditions of the instrument are as follows:

[0124] Instrument operating parameters: high frequency power: 1100W; plasma gas flow rate: 15L min -1 ; Auxiliary gas flow: 1.5Lmin -1 ; Atomizing gas flow rate: 0.75L min -1 ; Injection pump speed: 15rpm; Observation height: 10mm.

[0125] The experimental method is as follows:

[0126] (1) Accurately weigh 0.1 g of sample into a clean quartz crucible, place it in a box furnace, and gradually heat it to 930°C for ash treatment to obtain ash. The weight percentage of the sample reduced during the calcination process is the carbon content of the fibrous carbon-carbon composite material in the present invention;

[0127] (2) Use a small amount of ultrapure water to transfer all the ash into a PFA test tube, add aqua regia, hydrogen peroxide, sulfuric acid and hydrofluoric acid in sequence, cover and place in an electric heating digestion instrument to heat until the sample is completely digested;

[0128] (3) Remove the test tube and cool it to room temperature. Use ultrapure water to transfer it to a 50 mL volumetric flask and make up to volume for testing.

[0129] (4) preparing a mixed standard solution of the elements, drawing a test spectrum, detecting the solution to be tested using an inductively coupled plasma spectrometer, and calculating the content of each element according to the drawn test spectrum;

[0130] Selection of element spectral lines Inductively coupled plasma emission spectrometry can select multiple characteristic spectral lines for each element at the same time, and has a synchronous background correction function. Therefore, in the experiment, 4 spectral lines are selected for each element to be measured. The intensity, interference and stability are comprehensively analyzed to select the analysis line with less spectral interference and higher precision.

[0131] Example 1

[0132] The method for preparing the carbon-carbon composite material comprises:

[0133] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0134] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 55:35:20:15:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 105:1:3:55.

[0135] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0136] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0137] The carbon-carbon composite material prepared in this embodiment (macroscopic morphology is shown in FIG. Figure 1 As shown in the figure, it can be seen that the carbon-carbon composite material is in the form of black fibers and has the following characteristics:

[0138] (1) The cross-sectional morphology of the carbon-carbon composite material was measured using a scanning electron microscope. Fig.10 As shown, the center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets with a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0139] (2) The carbon-carbon composite material is black, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0140] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a sodium content of 10.2 weight %; a potassium content of 6.3 weight %; a nickel content of 3.3 weight %; a lithium content of 2.9 weight %; a platinum content of 2.7 weight %; an iron content of 3.1 weight %; a chromium content of 0.1 weight %; and a vanadium content of 0.2 weight %; that is, the carbon-carbon composite material contains 50 weight % of carbon, 19.4 weight % of Group IA metal elements, 0.2 weight % of Group VB metal elements, 0.1 weight % of Group VIB metal elements and 9.1 weight % of Group VIII metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0141] The characteristics of step (1) and step (2) were obtained by using a ZEISS Merlin field emission scanning electron microscope and an X-ray energy spectrometer configured with a field emission scanning electron microscope of ZEISS Merlin, Germany;

[0142] from Figure 2-Figure 9 It can be seen from the element spectrum that the Na( Figure 2 )、K( Figure 3 )、Ni( Figure 4 )、Li( Figure 5 )、Pt( Figure 6 )、Fe( Figure 7 ) and Cr( Figure 8 ) and V( Fig. 9 ) are evenly distributed and are nanoparticles.

[0143] Example 2

[0144] The method for preparing the carbon-carbon composite material comprises:

[0145] In the presence of nitrogen (gas flow rate of 200 mL / min), chopped carbon fibers (specification 24K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 100 hours.

[0146] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 36:70:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 70:95:55:32:50:40:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 197:1:3:145.

[0147] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0148] A valve is provided on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 5mm. A filter is provided before the valve along the gas flow direction.

[0149] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0150] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 59:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.6mm, and the length is 6mm;

[0151] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.6 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.161:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.479:1.

[0152] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 53 weight %; sodium content of 6.9 weight %; potassium content of 9.3 weight %; nickel content of 5.2 weight %; lithium content of 3.1 weight %; platinum content of 4.7 weight %; iron content of 4.2 weight %; chromium content of 0.3 weight %; vanadium content of 0.1 weight %; that is, the carbon-carbon composite material contains 53 weight % carbon, 19.3 weight % IA group metal elements, 0.1 weight % VB group metal elements, 0.3 weight % VIB group metal elements and 14.1 weight % VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0153] Example 3

[0154] The method for preparing the carbon-carbon composite material comprises:

[0155] In the presence of nitrogen (gas flow rate of 300 mL / min), chopped carbon fibers (specification 50K, length 9 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 80 hours.

[0156] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 35:50:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 40:30:25:30:20:15:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 100:1:3:60.

[0157] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 30ppm.

[0158] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 15mm. A filter is installed before the valve along the gas flow direction.

[0159] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0160] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 9mm; the outer periphery of the single carbon fiber is surrounded by 8 layers of graphite sheets in a concentric circle structure, the thickness of the 8 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 8 layers of graphite sheets to the diameter of the single carbon fiber is 39:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 9mm;

[0161] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.08 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.182:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.540:1.

[0162] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 65 weight %; sodium content of 7.2 weight %; potassium content of 5.3 weight %; nickel content of 4.1 weight %; lithium content of 6.2 weight %; platinum content of 3.5 weight %; iron content of 3.1 weight %; chromium content of 0.5 weight %; vanadium content of 0.2 weight %; that is, the carbon-carbon composite material contains 65 weight % carbon, 18.7 weight % IA group metal elements, 0.2 weight % VB group metal elements, 0.5 weight % VIB group metal elements and 10.7 weight % VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0163] Example 4

[0164] The method for preparing the carbon-carbon composite material comprises:

[0165] In the presence of nitrogen (gas flow rate of 300 mL / min) atmosphere, chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 120 hours.

[0166] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 32:65:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 25:20:20:20:10:10:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 65:1:3:40.

[0167] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0168] A valve is provided on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 20 mm. A filter is provided before the valve along the gas flow direction.

[0169] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0170] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 43:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.6mm, and the length is 6mm;

[0171] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.3 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.180:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.551:1.

[0172] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 58 weight %; sodium content of 7.0 weight %; potassium content of 5.1 weight %; nickel content of 3.9 weight %; lithium content of 6.0 weight %; platinum content of 3.2 weight %; iron content of 2.8 weight %; chromium content of 0.7 weight %; vanadium content of 0.3 weight %. That is, the carbon-carbon composite material contains 58 weight % of carbon, 18.1 weight % of IA group metal elements, 0.3 weight % of VB group metal elements, 0.7 weight % of VIB group metal elements and 9.9 weight % of VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0173] Example 5

[0174] The method for preparing the carbon-carbon composite material comprises:

[0175] In the presence of nitrogen (gas flow rate of 300 mL / min) atmosphere, chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 36 hours.

[0176] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 35:50:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 180:180:120:100:85:35:10:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 460:1:10:240.

[0177] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 30ppm.

[0178] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0179] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0180] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 57:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.8mm and the length is 6mm;

[0181] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.3 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.187:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.555:1.

[0182] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 73 weight %; sodium content of 9.2 weight %; potassium content of 6.2 weight %; nickel content of 2.3 weight %; lithium content of 2.1 weight %; platinum content of 1.7 weight %; iron content of 1.7 weight %; chromium content of 0.3 weight %; vanadium content of 0.2 weight %. That is, the carbon-carbon composite material contains 73 weight % of carbon, 17.5 weight % of IA group metal elements, 0.2 weight % of VB group metal elements, 0.3 weight % of VIB group metal elements and 5.7 weight % of VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0183] Example 6

[0184] The method for preparing the carbon-carbon composite material comprises:

[0185] In the presence of nitrogen (gas flow rate of 100 mL / min) atmosphere, chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 120 hours.

[0186] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 31:65:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 180:170:110:100:40:20:10:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 450:1:10:170.

[0187] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 20ppm.

[0188] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0189] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0190] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 98:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 1.0mm, and the length is 6mm;

[0191] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.5 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.187:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.553:1.

[0192] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 55 weight %; sodium content of 11.2 weight %; potassium content of 8.3 weight %; nickel content of 5.3 weight %; lithium content of 7.1 weight %; platinum content of 2.2 weight %; iron content of 1.1 weight %; chromium content of 0.5 weight %; vanadium content of 0.15 weight %. That is, the carbon-carbon composite material contains 55 weight % of carbon, 26.6 weight % of IA group metal elements, 0.15 weight % of VB group metal elements, 0.5 weight % of VIB group metal elements and 8.6 weight % of VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0193] Example 7

[0194] The method for preparing the carbon-carbon composite material comprises:

[0195] In the presence of nitrogen (gas flow rate of 200 mL / min), chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 120 hours.

[0196] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 32:66:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 180:180:150:100:60:40:10:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 460:1:10:250.

[0197] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 20ppm.

[0198] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0199] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0200] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 39:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 6mm;

[0201] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.6 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.182:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.553:1.

[0202] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 54 weight %; sodium content of 12.2 weight %; potassium content of 10.3 weight %; nickel content of 6.3 weight %; lithium content of 8.1 weight %; platinum content of 1.8 weight %; iron content of 1.2 weight %; chromium content of 0.7 weight %; vanadium content of 0.3 weight %. That is, the carbon-carbon composite material contains 54 weight % of carbon, 30.6 weight % of IA group metal elements, 0.3 weight % of VB group metal elements, 0.7 weight % of VIB group metal elements and 9.3 weight % of VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0203] Example 8

[0204] The method for preparing the carbon-carbon composite material comprises:

[0205] In the presence of nitrogen (gas flow rate of 300 mL / min), chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 72 hours.

[0206] The weight ratio of metal source, amorphous graphite and chopped carbon fiber is 58:115:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 110:80:50:30:20:10:6:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 220:1:6:80.

[0207] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 20ppm.

[0208] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0209] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0210] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 50:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.5mm, and the length is 6mm;

[0211] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.0 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.182:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.554:1.

[0212] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 69 weight %; sodium content of 7.2 weight %; potassium content of 5.3 weight %; nickel content of 3.2 weight %; lithium content of 2.2 weight %; platinum content of 1.2 weight %; iron content of 2.7 weight %; chromium content of 0.4 weight %; vanadium content of 0.37 weight %. That is, the carbon-carbon composite material contains 69 weight % of carbon, 14.7 weight % of IA group metal elements, 0.37 weight % of VB group metal elements, 0.4 weight % of VIB group metal elements and 7.1 weight % of VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0213] Example 9

[0214] The method for preparing the carbon-carbon composite material comprises:

[0215] In the presence of nitrogen (gas flow rate of 300 mL / min), chopped carbon fibers (specification 12K, length 6 mm, carbon content 95 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 48 hours.

[0216] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 70:140:1, and the metal source is sodium source (NaF), potassium source (KF), nickel source (NiCl 2 )、LiOH、PtO 2 ), iron source (Fe 2 O 3 ), chromium source (K 2 CrO 4 ) and vanadium source (VO 2), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 45:30:25:10:20:15:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 85:1:3:60.

[0217] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2800°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 20ppm.

[0218] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0219] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0220] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 89:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.9mm, and the length is 6mm;

[0221] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 1.2 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.180:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.555:1.

[0222] (3) The main elements contained in the carbon-carbon composite material include: 87 weight % carbon, 2.2 weight % sodium, 1.5 weight % potassium, 1.2 weight % nickel, 1.5 weight % lithium, 1.0 weight % platinum, 1.7 weight % iron, 0.1 weight % chromium, and 0.35 weight % vanadium. That is, the carbon-carbon composite material contains 87 weight % carbon, 5.2 weight % IA group metal elements, 0.35 weight % VB group metal elements, 0.1 weight % VIB group metal elements, and 3.9 weight % VIII group metal elements. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead, and strontium.

[0223] Example 10

[0224] The method of Example 1 is followed, except that the metal source is a potassium source, a nickel source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source, and no sodium source is included.

[0225] The method for preparing the carbon-carbon composite material comprises:

[0226] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0227] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is potassium source (KCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 35:20:15:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 50:1:3:55.

[0228] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0229] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0230] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0231] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0232] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0233] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 50 weight %; potassium content of 6.4 weight %; nickel content of 3.1 weight %; lithium content of 2.7 weight %; platinum content of 2.9 weight %; iron content of 3.5 weight %; chromium content of 0.3 weight %; vanadium content of 0.3 weight %. That is, the carbon-carbon composite material contains 50 weight % of carbon, 9.1 weight % of IA group metal elements, 0.3 weight % of VB group metal elements, 0.3 weight % of VIB group metal elements and 9.5 weight % of VIII group metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0234] Embodiment 11

[0235] The method of Example 1 is followed, except that the metal source is a sodium source, a nickel source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source, and no potassium source is included.

[0236] The method for preparing the carbon-carbon composite material comprises:

[0237] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0238] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 55:20:15:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 70:1:3:55.

[0239] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0240] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0241] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0242] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0243] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0244] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a sodium content of 10.5 weight %; a nickel content of 3.2 weight %; a lithium content of 2.6 weight %; a platinum content of 2.6 weight %; an iron content of 3.3 weight %; a chromium content of 0.1 weight %; and a vanadium content of 0.4 weight %; that is, the carbon-carbon composite material contains 50 weight % of carbon, 13.1 weight % of Group IA metal elements, 0.4 weight % of Group VB metal elements, 0.1 weight % of Group VIB metal elements and 9.1 weight % of Group VIII metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0245] Example 12

[0246] The method of Example 1 is followed, except that the metal source is a sodium source, a potassium source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source, and no nickel source is included.

[0247] The method for preparing the carbon-carbon composite material comprises:

[0248] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0249] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), lithium source (LiF), platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, lithium source, platinum source, iron source, chromium source and vanadium source is 55:35:15:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 105:1:3:35.

[0250] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0251] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0252] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0253] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0254] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0255] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 50 weight %; sodium content of 10.7 weight %; potassium content of 6.7 weight %; lithium content of 2.8 weight %; platinum content of 2.8 weight %; iron content of 3.4 weight %; chromium content of 0.2 weight %; vanadium content of 0.1 weight %. That is, the carbon-carbon composite material contains 50 weight % carbon, 20.2 weight % IA group metal elements, 0.1 weight % VB group metal elements, 0.2 weight % VIB group metal elements and 6.2 weight % VIII group metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0256] Embodiment 13

[0257] The method of Example 1 is followed, except that the metal source is a sodium source, a potassium source, a nickel source, a platinum source, an iron source, a chromium source and a vanadium source, and no lithium source is included.

[0258] The method for preparing the carbon-carbon composite material comprises:

[0259] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0260] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 )、Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, platinum source, iron source, chromium source and vanadium source is 55:35:20:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 90:1:3:55.

[0261] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume and the oxygen content is 40ppm.

[0262] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0263] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0264] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0265] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0266] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 50 weight %; sodium content of 10.4 weight %; potassium content of 6.5 weight %; nickel content of 3.5 weight %; platinum content of 2.5 weight %; iron content of 3.6 weight %; chromium content of 0.2 weight %; vanadium content of 0.1 weight %. That is, the carbon-carbon composite material contains 50 weight % carbon, 16.9 weight % IA group metal elements, 0.1 weight % VB group metal elements, 0.2 weight % VIB group metal elements and 9.6 weight % VIII group metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0267] Embodiment 14

[0268] The method of Example 1 is followed, except that the metal source is a sodium source, a potassium source, a nickel source, a lithium source, an iron source, a chromium source and a vanadium source, and no platinum source is included.

[0269] The method for preparing the carbon-carbon composite material comprises:

[0270] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0271] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 ), lithium source (LiF), iron source (FeCl 3), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, iron source, chromium source and vanadium source is 55:35:20:15:20:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 105:1:3:40.

[0272] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume and the oxygen content is 40ppm.

[0273] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0274] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0275] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0276] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0277] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a sodium content of 10.6 weight %; a potassium content of 6.5 weight %; a nickel content of 3.4 weight %; a lithium content of 2.5 weight %; an iron content of 3.2 weight %; a chromium content of 0.3 weight %; and a vanadium content of 0.3 weight %; that is, the carbon-carbon composite material contains 50 weight % of carbon, 19.6 weight % of Group IA metal elements, 0.3 weight % of Group VB metal elements, 0.3 weight % of Group VIB metal elements, and 6.6 weight % of Group VIII metal elements; elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead, and strontium.

[0278] Embodiment 15

[0279] The method of Example 1 is followed, except that the metal source is a sodium source, a potassium source, a nickel source, a lithium source, a platinum source, a chromium source and a vanadium source, and does not contain an iron source.

[0280] The method for preparing the carbon-carbon composite material comprises:

[0281] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0282] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, chromium source and vanadium source is 55:35:20:15:15:3:1, that is, the weight ratio of the IA group metal source, VB group metal source, VIB group metal source and VIII group metal source is 105:1:3:35.

[0283] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume and the oxygen content is 40ppm.

[0284] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0285] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0286] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 25:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.25mm, and the length is 3mm;

[0287] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0288] (3) The main elements contained in the carbon-carbon composite material include: 50 weight % carbon; 10.4 weight % sodium; 6.2 weight % potassium; 3.3 weight % nickel; 2.7 weight % lithium; 2.4 weight % platinum; 0.1 weight % chromium; 0.2 weight % vanadium; that is, the carbon-carbon composite material contains 50 weight % carbon, 19.3 weight % Group IA metal elements, 0.2 weight % Group VB metal elements, 0.1 weight % Group VIB metal elements and 5.7 weight % Group VIII metal elements; elements with a content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0289] Comparative Example 1

[0290] The method of Example 1 is implemented, except that short-cut carbon fibers are not added; a composite material is obtained;

[0291] The composite material obtained in this comparative example is in block form, and the composite material contains 99.9% by weight of carbon, and does not contain sodium, potassium, nickel, lithium, platinum, iron, chromium and vanadium. Elements with a content of less than 0.001% by weight include: zinc, manganese, silver, barium, copper, magnesium and strontium. Due to the lack of short-cut carbon fibers, the metal particles cannot form growth attachment points, and the carbon vapor can only grow into block-shaped carbon-containing substances with extremely high carbon content on the surface of the inner wall of the high-temperature furnace.

[0292] In this comparative example, since chopped carbon fibers were not used, the carbon-carbon composite material of the present invention could not be obtained.

[0293] Comparative Example 2

[0294] The method of Example 1 is carried out, except that there is no inert atmosphere protection during the reaction process; a composite material is obtained;

[0295] The composite material prepared in this comparative example contains 99.9% by weight of carbon, and does not contain sodium, potassium, nickel, lithium, platinum, iron, chromium and vanadium. The elements with a content of less than 0.001% by weight include zinc, manganese, silver, barium, copper, magnesium and strontium.

[0296] In this comparative example, since there is no inert atmosphere protection, the carbon-carbon composite material of the present invention cannot be obtained.

[0297] Comparative Example 3

[0298] The method of Example 1 is followed, except that no carbonized resin powder and metal source are added to the high temperature furnace.

[0299] No product was generated in this comparative example.

[0300] Comparative Example 4

[0301] The method of Example 1 is implemented, except that the central temperature of the high-temperature furnace is 1200°C; at this time, the reaction temperature is too low to volatilize the carbon in the carbonized resin powder and further grow on the surface of the carbon fiber, and the metal particles cannot adhere to the surface of the carbon fiber.

[0302] Therefore, no product was generated in this comparative example.

[0303] Comparative Example 5

[0304] The method of Example 1 was followed, except that the gas flow rate was 2000 mL / min. At this time, due to the excessive gas flow rate, the microenvironment for the stable growth of graphite sheets could not be maintained, and the metal particles could not adhere to the surface of the carbon fibers or graphite sheets.

[0305] Therefore, no product was generated in this comparative example.

[0306] Comparative Example 6

[0307] The method of Example 1 was followed, except that the gas flow rate was 10 mL / min;

[0308] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0309] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by two layers of graphite sheets with a concentric circle structure, the thickness of the two layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the two layers of graphite sheets to the diameter of the single carbon fiber is 3:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.03mm, and the length is 3mm;

[0310] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.02 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.161:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.474:1.

[0311] (3) The main elements contained in the carbon-carbon composite material include: 96 weight % carbon; 0.2 weight % sodium; 0.3 weight % potassium; 0.3 weight % nickel; 0.5 weight % lithium; 0.1 weight % platinum; 0.1 weight % iron; 0.1 weight % chromium; 0.2 weight % vanadium; that is, the carbon-carbon composite material contains 96 weight % carbon, 1 weight % Group IA metal elements, 0.2 weight % Group VB metal elements, 0.1 weight % Group VIB metal elements and 0.5 weight % Group VIII metal elements, and the elements with a content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, magnesium, lead and strontium.

[0312] Comparative Example 7

[0313] The method of Example 1 was followed, except that no metal source was added.

[0314] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0315] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 9 layers of graphite sheets in a concentric circle structure, the thickness of the 9 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 9 layers of graphite sheets to the diameter of the single carbon fiber is 19:1; the diameter of the carbon-carbon composite material is 0.2mm, and the length is 3mm;

[0316] (2) The carbon-carbon composite material is gray, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.07 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.159:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.479:1.

[0317] (3) The main elements contained in the carbon-carbon composite material include: carbon content is 99.9 weight %; elements with content less than 0.001 weight % include: zinc, manganese, silver, barium, copper, lithium, magnesium and strontium.

[0318] Comparative Example 8

[0319] The method of Example 1 was followed, except that no carbonized resin powder was added.

[0320] At this point, no product was generated in this comparative example.

[0321] Comparative Example 9

[0322] The method of Example 1 is followed, except that the metal source does not contain a sodium source, a potassium source, or a lithium source, that is, does not contain a Group IA metal source.

[0323] The method for preparing the carbon-carbon composite material comprises:

[0324] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0325] The weight ratio of the metal source, carbon resin powder and chopped carbon fiber is 50:100:1, and the metal source is nickel source (NiF 2 )、Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the nickel source, platinum source, iron source, chromium source and vanadium source is 20:15:20:3:1, that is, the weight ratio of the VB group metal source, the VIB group metal source and the VIII group metal source is 1:3:55.

[0326] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0327] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0328] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0329] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 18:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.20mm, and the length is 3mm;

[0330] (2) The carbon-carbon composite material is black, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.03 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.161:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.482:1.

[0331] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a nickel content of 3.5 weight %; a platinum content of 2.8 weight %; an iron content of 3.2 weight %; a chromium content of 0.1 weight %; and a vanadium content of 0.2 weight %, that is, the carbon-carbon composite material contains 50 weight % carbon, 0.2 weight % VB group metal elements, 0.1 weight % VIB group metal elements and 9.5 weight % VIII group metal elements; elements whose content is less than 0.001 weight % include: zinc, manganese, silver, barium, magnesium, lead and strontium.

[0332] Comparative Example 10

[0333] The method of Example 1 is followed, except that the metal source does not contain an iron source, a platinum source, or a nickel source, that is, does not contain a Group VIII metal source.

[0334] The method for preparing the carbon-carbon composite material comprises:

[0335] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0336] The weight ratio of the metal source, carbon resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), lithium source (LiF), chromium source (Li 2 CrO 4 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, lithium source, chromium source and vanadium source is 55:35:15:3:1, that is, the weight ratio of the IA group metal source, VB group metal source and VIB group metal source is 105:1:3.

[0337] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0338] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0339] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0340] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 18:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.18mm, and the length is 3mm;

[0341] (2) The carbon-carbon composite material is black, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.02 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.160:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.481:1.

[0342] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a sodium content of 10.3 weight %; a potassium content of 6.5 weight %; a lithium content of 3.1 weight %; a chromium content of 0.1 weight %; and a vanadium content of 0.2 weight %, that is, the carbon-carbon composite material contains 50 weight % of carbon, 19.9 weight % of Group IA metal elements, 0.2 weight % of Group VB metal elements and 0.1 weight % of Group VIB metal elements; elements whose content is less than 0.001 weight % include: zinc, manganese, silver, barium, magnesium, lead and strontium.

[0343] Comparative Example 11

[0344] The method of Example 1 is followed, except that the metal source does not contain a vanadium source, that is, does not contain a VB group metal source.

[0345] The method for preparing the carbon-carbon composite material comprises:

[0346] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0347] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ) and chromium source (Li 2 CrO 4 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source and chromium source is 55:35:20:15:15:20:3, that is, the weight ratio of the IA group metal source, the VIB group metal source and the VIII group metal source is 105:3:55.

[0348] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0349] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0350] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0351] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 18:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.19mm, and the length is 3mm;

[0352] (2) The carbon-carbon composite material is black, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.03 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.162:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1.

[0353] (3) The main elements contained in the carbon-carbon composite material include: a carbon content of 50 weight %; a sodium content of 10.3 weight %; a potassium content of 6.4 weight %; a nickel content of 3.4 weight %; a lithium content of 2.7 weight %; a platinum content of 2.5 weight %; an iron content of 3.0 weight %; and a chromium content of 0.1 weight %; that is, the carbon-carbon composite material contains 50 weight % of carbon, 19.4 weight % of Group IA metal elements, 0.1 weight % of Group VIB metal elements, and 8.9 weight % of Group VIII metal elements; elements whose content is less than 0.001 weight % include: zinc, manganese, silver, barium, magnesium, lead, and strontium.

[0354] Comparative Example 12

[0355] The method of Example 1 is followed, except that the metal source does not contain a chromium source, that is, does not contain a VIB Group metal source.

[0356] The method for preparing the carbon-carbon composite material comprises:

[0357] In the presence of nitrogen (gas flow rate of 100 mL / min), chopped carbon fibers (specification 12K, length 3 mm, carbon content 90 wt%), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0358] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 50:100:1, and the metal source is sodium source (NaCl), potassium source (KCl), nickel source (NiF 2 )、Lithium source (LiF), Platinum source (Pt(OH) 2 ), iron source (FeCl 3 ) and vanadium source (V 2 O 3 ), the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source and vanadium source is 55:35:20:15:15:20:1, that is, the weight ratio of the IA group metal source, VB group metal source and VIII group metal source is 105:1:55.

[0359] The high temperature furnace uses isostatic graphite as the heating element. The central temperature of the high temperature furnace is 2200°C. The purity of the nitrogen atmosphere is 99.99% by volume, and the oxygen content is 40ppm.

[0360] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0361] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0362] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 18:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.22mm, and the length is 3mm;

[0363] (2) The carbon-carbon composite material is black, and each graphite sheet has independent carbon particles distributed on its surface, with a particle size of 0.02 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of its surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.159:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.478:1.

[0364] (3) The main elements contained in the carbon-carbon composite material include: 50 weight % carbon; 10.4 weight % sodium; 6.5 weight % potassium; 3.6 weight % nickel; 2.6 weight % lithium; 2.4 weight % platinum; 3.1 weight % iron; 0.2 weight % vanadium; that is, the carbon-carbon composite material contains 50 weight % carbon, 19.5 weight % Group IA metal elements, 0.2 weight % Group VB metal elements and 9.1 weight % Group VIII metal elements; the elements whose content is less than 0.001 weight % include: zinc, manganese, silver, barium, magnesium, lead and strontium.

[0365] Test Example 1

[0366] The electrochemical properties of the carbon-carbon composite materials prepared in the examples and the composite materials and carbon-carbon composite materials obtained in the comparative examples were tested according to the following method (comparative examples 3-5 and comparative example 8 had no products generated, so the corresponding electrochemical properties could not be measured).

[0367] The catalytic activity was tested using a Chenhua electrochemical workstation (CHI760E) in conjunction with a rotating disk electrode. The test was carried out in a traditional three-electrode system, including a working electrode (rotating disk electrode), a reference electrode (saturated calomel electrode, Hg / HgO) and a counter electrode (platinum wire), and the electrolyte was 0.1M KOH.

[0368] The electrode potential is converted to the potential relative to the standard hydrogen electrode. Before the test, the working electrode needs to be strictly polished, and polished to a bright finish using alumina powders of different particle sizes (1um, 0.3um, and 0.05um), and then cleaned with ethanol and water and dried for use.

[0369] First, N was introduced into the electrolyte. 2 or 2 , at least 30 min until the gas is saturated, and then immersed in the prepared working electrode coated with carbon-carbon composite material. In the potential range of 0-1.2 V, at 100 mV s -1 The surface of the working electrode was cleaned at a rate of 50 mV s -1 The rate of desorption was tested. According to the integrated area of ​​the desorption peak region, the electrochemical active area (ECSA) of the carbon-carbon composite material can be calculated.

[0370] The calculation formula is as follows:

[0371]

[0372] Among them, Q H represents the amount of desorption, in mC; 0.21 represents the amount of hydrogen adsorbed and desorbed per unit area of ​​Pt atoms, in mC cm -2 ; m represents the Pt loading on the working electrode, in g.

[0373] The results are shown in Table 1:

[0374] Table 1

[0375]

[0376]

[0377] It can be seen from the above results that the carbon-carbon composite material of the present invention includes a single carbon fiber and multiple layers of graphite sheets surrounding the outer periphery of the single carbon fiber, and nano-metal particles are filled between any two adjacent layers of graphite sheets, and both have a high electrochemical active area. The higher active surface can increase the aggregation concentration and migration rate of mobile charges, which is beneficial to increase the conductivity of the electrode material and has a better effect.

[0378] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A carbon-carbon composite material, characterized in that: The carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, and nano-metal particles are filled between any two adjacent layers of graphite sheets. The nano metal particles contain metal elements of Group IA, Group VB, Group VIB and Group VIII.

2. The carbon-carbon composite material according to claim 1, characterized in that: The carbon-carbon composite material contains 45-92 weight % of carbon elements, 1.6-52 weight % of IA group metal elements, 0.1-1 weight % of VB group metal elements, 0.05-3 weight % of VIB group metal elements and 2.2-33 weight % of VIII group metal elements.

3. The carbon-carbon composite material according to claim 1 or 2, characterized in that: The nano metal particles contain sodium, potassium, nickel, lithium, platinum, iron, chromium and vanadium; Preferably, the carbon-carbon composite material contains 45-92 weight % of carbon, 0.7-18 weight % of sodium, 0.5-18 weight % of potassium, 0.5-15 weight % of nickel, 0.4-13 weight % of lithium, 1-10 weight % of platinum, 0.7-8 weight % of iron, 0.05-3 weight % of chromium and 0.1-1 weight % of vanadium; Preferably, the carbon-carbon composite material contains 50-90 weight % of carbon, 1-15 weight % of sodium, 1-15 weight % of potassium, 1-10 weight % of nickel, 1-10 weight % of lithium, 1-5 weight % of platinum, 1-5 weight % of iron, 0.1-1 weight % of chromium and 0.1-0.5 weight % of vanadium.

4. The carbon-carbon composite material according to any one of claims 1 to 3, characterized in that: The number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, preferably 8-12 layers.

5. The carbon-carbon composite material according to any one of claims 1 to 4, characterized in that: The diameter of the single carbon fiber is 4-8um, preferably 4.5-7.5um; Preferably, the length of the single carbon fiber is 2-10 mm, preferably 3-9 mm.

6. The carbon-carbon composite material according to any one of claims 1 to 5, characterized in that: The thickness of the multilayer graphite sheet increases gradually from the inside to the outside; Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:

1.

7. The carbon-carbon composite material according to any one of claims 1 to 6, characterized in that: The carbon-carbon composite material is in a straight line or a curved shape; Preferably, at least part of the surface of the carbon-carbon composite material is in a bamboo-node shape and / or a convex shape; Preferably, the diameter of the carbon-carbon composite material is 0.05-1 mm, preferably 0.1-0.3 mm; Preferably, the length of the carbon-carbon composite material is 0.1-10 mm, preferably 1-5 mm.

8. The carbon-carbon composite material according to any one of claims 1 to 7, characterized in that: In the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1; Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak is 0.2-0.9:

1.

9. A method for preparing a carbon-carbon composite material, characterized in that: The method comprises: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 50-500 mL / min; The metal source includes a Group IA metal source, a Group VB metal source, a Group VIB metal source and a Group VIII metal source.

10. The method according to claim 9, characterized in that The weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:

1.

11. The method according to claim 9 or 10, characterized in that: The weight ratio of the IA group metal source, the VB group metal source, the VIB group metal source and the VIII group metal source is 50-500:1:3-10:30-350.

12. The method according to claims 9-11, characterized in that: The metal source contains a sodium source, a potassium source, a nickel source, a lithium source, a platinum source, an iron source, a chromium source and a vanadium source; Preferably, the weight ratio of the sodium source, potassium source, nickel source, lithium source, platinum source, iron source, chromium source and vanadium source is 20-180:20-180:20-150:10-100:10-100:5-80:3-10:

1.

13. The method according to claim 12, characterized in that The sodium source is selected from one or more of Na2CO3, NaHCO3, NaNO3, NaCl and NaF; Preferably, the potassium source is selected from one or more of KCl, K2CO3, KF and KOH; Preferably, the nickel source is selected from one or more of NiO, Ni(OH)2, NiF2 and NiCl2; Preferably, the lithium source is selected from one or more of LiF, Li2O, LiOH and LiCl; Preferably, the platinum source is selected from one or more of PtO, PtO2 and Pt(OH)2; Preferably, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4; Preferably, the chromium source is selected from one or more of CrO3, Li2CrO4, K2CrO4 and BaCrO4; Preferably, the vanadium source is selected from one or more of VO, V2O3, VO2 and V2O5.

14. The method according to claim 9, characterized in that The carbon source is carbonized resin and / or graphite; Preferably, the graphite is amorphous graphite.

15. The method according to claim 9, characterized in that The reaction temperature is 1500-3000°C; Preferably, the reaction time is 12-720 hours, more preferably 24-120 hours; Preferably, the volume flow rate of the inert atmosphere is 100-300 mL / min.

16. The method according to any one of claims 9, 13-15, characterized in that: The length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; Preferably, the specification of the chopped carbon fiber is 12-320K, preferably 12-48K; Preferably, the carbon content of the chopped carbon fibers is 85-95% by weight.

17. A carbon-carbon composite material prepared by the method according to any one of claims 9 to 16.

18. Use of the carbon-carbon composite material according to any one of claims 1 to 8 or the carbon-carbon composite material according to claim 17 in graphite electrode materials.

Citation Information

Patent Citations

  • Carbon-carbon composite material as well as preparation process and application thereof

    CN111807853A

  • Manufacturing process of carbon-carbon composite material

    CN112125690A

  • Preparation method of flexible carbon-carbon composite material

    CN112679950A

  • Thin-wall high-strength carbon-carbon composite material pipeline and preparation method thereof

    CN113175565A

  • Carbon nano tube deposited carbon-carbon composite material

    CN113636854A